Infinitely Many Solutions for an Elliptic Problem with Critical Exponent in Exterior Domain (Journal of Partial Differential Equations, 2018)
We consider the following nonlinear problem -Δu=u^{\frac{N+2}{N-2}}, u > 0, in R^N\Ω, u(x)→ 0, as |x|→+∞, \frac{∂u}{∂n}=0, on ∂Ω, where Ω⊂R^N N ≥ 4 is a smooth and bounded domain and n denotes inward normal vector of ∂Ω. We prove that the above problem has infinitely many solutions whose energy can be made arbitrarily large when Ω is convex seen from inside (with some symmetries).
Keywords: Infinitely many solutions; critical exponent; exterior domain